CORPORATE GOVERNANCE DAN KETAATAN PENGUNGKAPAN WAJIB PADA BADAN USAHA MILIK NEGARA - Abdul Kharis; Djoko Suhardjanto (University of Merdeka Malang, 2012)
The purpose of this study was to examine corporate governance and mandatory disclosures compliance ofIndonesian BUMN (Badan Usaha Milik Negara). Under purposive sampling, secondary data of 48 annualreports year 2005-2010 of BUMN in Indonesian Stock Exchange were selected.The average level of mandatorydisclosures compliance was at 54.99%. This number indicated that Indonesians BUMN was not fullycompliance to SE Bapepam No. SE-02/PM/2002 and SE-02/BL/2008. In accordance with the purpose of thestudy, the result of multiple regression showed that corporate governance affected the level of mandatorydisclosure compliance through the variable number of board and educational background of director. Othervariables, such as board size, the composition of independent commissioner, audit committee size, the compositionof independent audit committee members and number of audit committee meetings were not good predictorsfor level of mandatory disclosure compliance.